2006
DOI: 10.1063/1.2193401
|View full text |Cite
|
Sign up to set email alerts
|

Ni Schottky diodes on cubic GaN

Abstract: Schottky diodes were fabricated by thermal evaporation of nickel on phase-pure cubic GaN(c-GaN) layers grown by plasma assisted molecular beam epitaxy on freestanding 3C-SiC. Detailed analysis of the I-V characteristics revealed the existence of a thin surface barrier at the Ni-semiconductor interface. Thermal annealing in air at 200°C alters the composition of this thin surface barrier, reduces the leakage current by three orders of magnitude, and increases the breakdown voltage. The dependence of the breakdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
5
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…This is in good agreement with earlier findings where it was found that annealing of metal contacts on c-III-nitrides reduces the leakage current significantly [14], [15]. Then c-AlGaN/GaN mesas were formed by SiCl 4 RIE in order to separate single devices.…”
Section: Methodssupporting
confidence: 92%
“…This is in good agreement with earlier findings where it was found that annealing of metal contacts on c-III-nitrides reduces the leakage current significantly [14], [15]. Then c-AlGaN/GaN mesas were formed by SiCl 4 RIE in order to separate single devices.…”
Section: Methodssupporting
confidence: 92%
“…[23][24][25][26][27] As thermal stability of metal contacts is important for device operations at high temperatures and in harsh environments, several authors studied the effect of high temperature furnace annealing on Schottky barrier parameters in GaN based devices. [28][29][30][31] In most of these reports, furnace annealing is done for a relatively longer period (5-60 min) where Schottky barriers are found to degrade with increase in annealing temperature. For example, a reduction in SBH in Ni/GaN is observed upon annealing due to reaction of Ni with GaN forming various phases like Ga 4 Ni 3 , Ga 4 Ni 2 , etc.…”
mentioning
confidence: 99%
“…Capacitance-voltage (C-V) measurements on cubic AlGaN/GaN metal-oxide-semiconductor (MOS) structures [12,13] and on Schottky diodes [14][15][16] showed in unintentially doped epilayers a background carrier concentration N D -N A of about 9x10 16 -2x10 17 cm -3 for the cubic GaN Table 1 and are used in our self-consistent band structure calculations. In Fig.…”
Section: Methodsmentioning
confidence: 99%